High Performance Aqueous Li-Ion Flow Capacitor Realized Through Microstructure Design of Suspension Electrode - Cao, Defu; Bai, Xiaojie; Wang, Junhui; Liu, Hao; Liao, Libing (Frontiers in Chemistry, 2021)
Suspension electrode is the core of flowable electrochemical energy storage systems, which are considered suitable for large-scale energy storage. Nevertheless, obtaining suspension electrodes with both low viscosity and high conductivity is still a big challenge. In present work, spinel LiMn2O4 was chosen as an example to make suspension with low viscosity and high conductivity through microstructure morphology control of solid particles and the contact mode between active materials and conductive additives in suspension electrode. By coating a thin layer of polyaniline on the surface of spherical spinel LiMn2O4, the resulting suspension showed much higher electronic conductivity (about 10 times) and lower viscosity (about 4.5 times) as compared to irregular and bare spinel LiMn2O4-based suspension counterpart. As a result, the Li-ion flow capacitor based on LiMn2O4 and activated carbon suspensions exhibited a record energy density of 27.4 W h L−1 at a power density of 22.5 W L−1 under static condition to date, and can be smoothly work under an intermittent-flow mode. The strategy reported in this work is an effective way for obtaining suspension electrodes with low viscosity and high electronic conductivity simultaneously. It can not only be used in the flow capacitors, but also can be extended to other flowable electrochemical energy storage systems.